Pure Organic Active Compounds Against Abiotic Stress: A Biostimulant Overview - García-García, Ana L.; García-Machado, Francisco J.; Borges, Andrés A.; Morales-Sierra, Sarai; Boto, Alicia; Jiménez-Arias, David (Frontiers in Plant Science, 2020)
Biostimulants (BSs) are probably one of the most promising alternatives nowadays to cope with yield losses caused by plant stress, which are intensified by climate change. Biostimulants comprise many different compounds with positive effects on plants, excluding pesticides and chemical fertilisers. Usually mixtures such as lixiviates from proteins or algal extracts have been used, but currently companies are interested in more specific compounds that are capable of increasing tolerance against abiotic stress. Individual application of a pure active compound offers researchers the opportunity to better standarise formulations, learn more about the plant defence process itself and assist the agrochemical industry in the development of new products. This review attempts to summarise the state of the art regarding various families of organic compounds and their mode/mechanism of action as BSs, and how they can help maximise agricultural yields under stress conditions aggravated by climate change.